Ethnobotanical study of wild and semi-wild edible plants in Yeki district, Sheka Zone, Southwest Ethiopia - Ashebir Awoke; Yared Siyum; Girma Gudesho; Fetku Akmel; Kiros Shiferaw Abate (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Wild and semi-wild edible plants (WSWEPs) play a critical role in sustaining rural livelihoods by contributing to food security, nutrition, traditional medicine, and cultural identity. In Yeki District, Sheka Zone, Southwest Ethiopia Region, Ethiopia, where diverse ethnic groups coexist, these plants remain integral to local diets and health practices. However, factors such as agricultural expansion and urbanization threaten their availability, highlighting the need for comprehensive ethnobotanical documentation and sustainable management. Methods This study employed a cross-sectional ethnobotanical survey conducted from November 2023 to August 2024 across five purposively selected kebeles. Data were collected through semi-structured interviews, focus group discussions, market surveys, and guided field walks involving 175 informants. Plant specimens were collected, identified, and documented following standard taxonomic references. Quantitative analyses, including preference ranking, direct matrix ranking, and statistical tests (t-tests, ANOVA), were applied to assess knowledge variations and threats. Results A total of 74 WSWEP species belonging to 34 families were identified, with herbs being the dominant growth form and fruits the most frequently used edible parts. Significant knowledge differences were observed based on gender, literacy, ethnicity, and informant experience. Agricultural expansion and urbanization were identified as the primary threats. Consumption modes varied, with 46% eaten raw and others (54%) prepared by boiling or cooking. Some plants required careful processing due to mild adverse effects reported during consumption. Conclusion WSWEPs in Yeki district are vital for nutrition, health, cultural heritage, and environmental sustainability. Conservation efforts, community education, and policy integration are essential to safeguard these resources. Further research into their nutritional and pharmacological potential could enhance their sustainable use and value.